การตรวจวัดอนุมูลอิสระในถั่วเหลือง ถั่วแดง ลูกเดือย และเม็ดบัวที่ฉายรังสี - สุมิตรา คำประกอบ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
An investigation on gamma irradiated Soybean, Kidneybean, Job s tear and Lotus seed samples by an ESR Spectrometer indicated that the amount of induced free radical varied directly to the irradiated gamma dose. The induced free radical of all samples had a maximum value after completion of irradiation, then decreased exponentially in the first 15 days period before becoming stable. No presence of microorganism was observed at a dose of 25 kGy